Dampak Kondisi Perumahan Terhadap Umur Harapan Hidup Saat Lahir Di Indonesia - Desvira, Tetri; Lusiani, Gustina; Kamarni, Neng; Purwasutrisno, Purwasutrisno (Universitas Negeri Padang, 2024)
Housing is a major health resource and an important environmental influence on health. One indicator of health can be seen in life expectancy at birth. Although life expectancy at birth in Indonesia has increased from year to year, globally, life expectancy at birth in Indonesia is still relatively low. This research aims to analyze the influence of the relationship between housing conditions and life expectancy at birth (UHH) in Indonesia. The data used is secondary data sourced from BPS covering 34 provinces from 2017-2022. The research approach is a quantitative approach with a panel data regression method. The research results show that residential area has a negative and significant influence on UHH at birth, while drinking water, proper sanitation, and ASI together have a positive and significant influence on UHH at birth. From this research, it is hoped that the government will pay more attention to the facilities and conditions of people's homes and identify what housing interventions are needed for public health policies. Then, with good housing facilities and conditions, it will improve the health level of the population.